Problemas de autovalores para o p-Laplaciano com distintas condições de fronteira - Pacheco, Rodrigo dos Santos (2019)
The goal of this work is to obtain, through the Ljusternik-Schnirelman principle, a sequence of eigenvalues for p-Laplacian with Dirichlet, Neumann and Robin-Steklov boundary conditions, the last one which is a combination of the Robin boundary conditions with Steklov boundary conditions. Moreover, we present a characterization for the regularity of the eigenfunctions and make an analysis of the spectrum of problems considered, especially, we will explore the rst eigenvalue of them.